Do Information Networks Enhance Adoption of Sustainable Agricultural Practices? Evidence from Northern Dry Zone of Karnataka, India - Niranjan, S.; Singh, D. R.; Kumar, N. R.; Jha, G. K.; Venkatesh, P.; Nain, M. S.; Krishnakumare, B (Indian Journal of Extension Education, 2022)
The study aimed to analyze the perception of farmers towards sustainable agricultural practices (SAPs) and identify social networks using primary data collected randomly from 300 farmers of the northern dry zone of Karnataka. Five-point Likert scale was used to analyze the perception of farmers towards SAPs and open-source software named “Gephi” was used to map farmers’ social networks. Farmers’ perceptions towards SAPs were poor and only one in eight respondents reported high perception towards SAPs. Comparatively, large farmers had better perception towards SAPs and had better access to capacity building (extension contact and farm events) than the small and marginal farmers. Social capital (neighbor, progressive and relative farmers) had also played an important role in spreading SAPs related information among the farmers. However, local input dealers failed to be key informants and hardly disseminated information regarding SAPs. Government extension officials were the dominant informants on SAPs. Given the low level of adoption of SAPs in the study area, exploiting the potential of ICTs, training local input dealers, capacity building of the farmers and effective utilization of social capital are the suggested policy options to enhance the adoption of SAPs.
Keywords: Sustainable agricultural practices (SAP); Perception; Information; Social network analysis (SNA); Degree centrality; Social capital; Capacity building